1981
DOI: 10.1017/s0007485300051026
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Glossina morsitans morsitans Westwood (Diptera: Glossinidae) sex Pheromone on behaviour of males in field and laboratory

Abstract: More adult males of Glossina morsitans morsitans Westw. were caught with hand nets in Tanzania from a man-carried dark screen baited with surrogate female decoys impregnated with synthetic 15,19,23-trimethylheptatriacontane (the G. m. morsitans sex pheromone) than from a screen bearing unimpregnated decoys or from a screen alone. A similar pattern was obtained with G. pallidipes Aust., but the variations in numbers of both species caught within and between fly-round sectors were large. Although many G. m. mors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

1982
1982
1993
1993

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…The cuticular hydrocarbon profiles of several taxa of Glossina were obtained using GC (Huyton et ah, 1980b;Carlson, 1981Carlson, , 1982Carlson, , 1988 during sex stimulant pheromone studies in a few species (Langley et al, 1981;Carlson et ah, 1984). Traditional phylogenetic relation-ships were supported in preliminary observations of GC profiles of 10 well studied species (Carlson, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…The cuticular hydrocarbon profiles of several taxa of Glossina were obtained using GC (Huyton et ah, 1980b;Carlson, 1981Carlson, , 1982Carlson, , 1988 during sex stimulant pheromone studies in a few species (Langley et al, 1981;Carlson et ah, 1984). Traditional phylogenetic relation-ships were supported in preliminary observations of GC profiles of 10 well studied species (Carlson, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…Initial experiments in Tanzania showed that wild males of G. m. morsitans visually attracted to a dark screen attempted to copulate with small objects on the screen if the objects were baited with sex pheromone (Langley et al, 1981). The duration of attempted copulation with these objects in the field was short by comparison with that measured in the laboratory and was influenced by the movement of the screen and probably by the presence of man in the experimental situation (Langley et al, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…Initial experiments in Tanzania showed that wild males of G. m. morsitans visually attracted to a dark screen attempted to copulate with small objects on the screen if the objects were baited with sex pheromone (Langley et al, 1981). The duration of attempted copulation with these objects in the field was short by comparison with that measured in the laboratory and was influenced by the movement of the screen and probably by the presence of man in the experimental situation (Langley et al, 1981). There is a complex interaction between the visual and olfactory stimuli associated with a variety of baits in the form of mobile or stationary inanimate models, men or host animals, and the sex and species composition of tsetse attracted to them (Vale, 1974a).…”
Section: Introductionmentioning
confidence: 99%
“…Male Diptera commonly chase and accost prospective mates in flight (Land & Collett, 1974;Collett & Land, 1975;Wehrhahn, 1979;Gibson, 1985), a facet of their behaviour that has attracted attention because of the potential it provides for analysing the mechanisms and precision of vision and visually controlled behaviour. Tsetse fly males are likewise attracted to female-sized targets (Vale, 1974;Langley et al, 1981;Hall, 1987), but the visual aspects of this behaviour have been examined only in Correspondence: Dr J. Brady, Imperial College, Silwood Park, Ascot, Berks. SL5 7PY. relation to attracting males to immobile dummy female 'baits' (see Hall, 1987;Wall, 1989).…”
Section: Introductionmentioning
confidence: 99%